2013
DOI: 10.1088/0029-5515/53/12/123009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ELM energy loss by pellet injection for ELM pacing

Abstract: The energy loss caused by the edge localized mode (ELM) needs to be reduced for ITER operations with ELMy H-mode plasmas. The reduction of ELM energy loss by the pellet injection for ELM pacing has been studied by an integrated core / scrape-off-layer (SOL) / divertor transport code TOPICS-IB with an MHD stability code and a pellet model taking account of the ExB drift of pellet plasma cloud. It is found that the energy loss can be reduced by a small pellet injected from the low-field-side (LFS), which penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…An alternative mechanism for ELM triggering by pellets was proposed in Ref. 127. From 2D transport modelling, it was concluded that the axisymmetric pressure profile steepens locally due to the absorption of energy by the pellet, leading to a destabilisation of a ballooning instability.…”
Section: Elm Control Methods: Pellet Pacingmentioning
confidence: 99%
“…An alternative mechanism for ELM triggering by pellets was proposed in Ref. 127. From 2D transport modelling, it was concluded that the axisymmetric pressure profile steepens locally due to the absorption of energy by the pellet, leading to a destabilisation of a ballooning instability.…”
Section: Elm Control Methods: Pellet Pacingmentioning
confidence: 99%
“…One method is to modify the conditions at the edge by injecting frozen deuterium pellets which quickly ionise [19][20][21][22][23][24], see also the topical review [25]. Pellet ELM pacing relies on the triggering of an ELM by the strong local perturbation created by the ablated particles deposited in the plasma edge.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that this scheme is related to a scheme of pellet injection at frequencies up to 45 times the natural f ELM proposed for use in ITER [9], and tested in DIII-D [8], and to a scheme modelled by Hayashi [20],who suggests that small pellets of the order of 1% of the pedestal particle content, which are fully ablated at the top of the pedestal, may be sufficient to trigger ELMs, and thereby reduce their size. However, significant ELM suppression may not occur unless the pellet rate significantly exceeds f ELM .…”
Section: Discussionmentioning
confidence: 99%
“…Injection of pellets to the top of the pedestal has been suggested to produce ELM pacing with reduced energy loss in * craig.bowie@anu.edu.au modelling by Hayashi [20], using the code TOPICS-IB. That modelling suggested that pellets with ∼1% of the pedestal particle content, with speed sufficient to reach the pedestal top, will reduce energy loss significantly.…”
Section: Introductionmentioning
confidence: 99%